Other logics : alternatives to formal logic in the history of thought and contemporary philosophy - Skodo, Admir. (Philosophy of History and Culture, 2014)
Other Logics: Alternatives to Formal Logic in the History of Thought and Contemporary Philosophy challenges the widespread idea of formal logic as inherently monolithic, universal, and ahistorical. Written by both leading and up-and-coming scholars, and edited by Admir Skodo, Other Logics offers a wide variety of historical and philosophical alternatives to this idea, all arguing that logic is a historical, concrete, and multi-dimensional phenomenon. To name a few examples, Frank Ankersmit lays down a representationalist logic, Alessandra Tanesini forcefully argues for the possibility of logical aliens, Christopher Watkin analyzes how leading contemporary French philosophers view the idea of logic, and Aaron Wendland unearths Heidegger's critique of formal logic. In Other Logics readers will find provocative interventions in a highly contested field in contemporary philosophy. Contributors include: Frank Ankersmit, Christopher Watkin, Giuseppina D'Oro, Alessandra Tanesini, Admir Skodo, Aaron Wendland, Ervik Cejvan, Anders Kraal, Christopher Fear, Karim Dharamsi, Johan Modée, and Thord Svensson.